Unveiling antimicrobial resistance in Chilean fertilized soils: a One Health perspective on environmental AMR surveillance - Fresno, Marcela; Pavez, Leonardo; Poblete, Yanina; Cortez, Alexandra; Del Pozo, Talía (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) poses a significant threat to humans and animals as well as the environment. Within agricultural settings, the utilization of antimicrobial agents in animal husbandry can lead to the emergence of antimicrobial resistance. In Chile, the widespread use of animal-derived organic amendments, including manure and compost, requires an examination of the potential emergence of AMR resulting from their application. The aim of this research was to identify and compare AMR genes found in fertilized soils and manure in Los Andes city, Chile. Soil samples were collected from an agricultural field, comprising unamended soils, amended soils, and manure used for crop fertilization. The selected genes (n=28) included genes associated with resistance to beta-lactams, tetracyclines, sulfonamides, polymyxins, macrolides, quinolones, aminoglycosides, as well as mobile genetic elements and multidrug resistance genes. Twenty genes were successfully identified in the samples. Tetracycline resistance genes displayed the highest prevalence, followed by MGE and sulfonamides, while quinolone resistance genes were comparatively less abundant. Notably, blaOXA, sulA, tetO, tetW, tetM, aac(6)ib, and intI1, exhibited higher frequencies in unamended soils, indicating their potential persistence within the soil microbiome and contribution to the perpetuation of AMR over time. Given the complex nature of AMR, it is crucial to adopt an integrated surveillance framework that embraces the One Health approach, involving multiple sectors, to effectively address this challenge. This study represents the first investigation of antimicrobial resistance genes in agricultural soils in Chile, shedding light on the presence and dynamics of AMR in this context.